EFFECTIVE WAY TO ESTIMATE THE STANDARD MINUTE VALUE (SMV) OF A T-SHIRT BY WORK STUDY - Rahman, Habibur; Roy, Prashanta Kumar; Karim, Rezaul; Biswas, Prodip Kumar (European Scientific Journal, ESJ, 2014)
This study is based on calculation of standard minute value (SMV) of a T-shirt by determining the manpower and machine allocation for particular target. An experimental investigation for the distribution of SMV for each and every operation requires for making a T-shirt and provides a clear and detail concepts for determining line balancing, machine requirements, man power allocation, operational sequence of the manufacturing process for setting a definite target within a reasonable efficiency. This study is a detailed discussion and distribution of SMV of a T-shirt by work study which will assist to minimize the SMV for having a better synchronization with man, machine, materials and methods to achieve higher efficiency. A general overview over efficient productive method to make a T-shirt is given in this paper.